Como incidó la pandemia del covid-19 en las ventas de la empresa Orocash de la ciudad de Guayaquil en el periodo 2020 - Melendez Martillo, Jessica Katherine (2021)
The covid-19 pandemic affected all commercial sectors, which integrates consumer decision-making, causing changes when managing a purchase, which has led to the closure of several businesses. Sales were the main indicator affected within companies by the pandemic, due to the stoppage of commercial activities, the economic impact at the national level, that is to say, the little flow of money due to the decrease in salaries and dismissal of employees. However, this phenomenon influenced organizations to enter the digital world en masse, helping to maintain customer attraction, being one of the means that has generated the greatest influence on sales, allowing companies to better their profitability and greater acquisition of sales, also serving as a means of market analysis in order to know current needs as one of the main tools to be able to access products and services from an application for fear of infection.